Colorimetric Determination of Baclofen with Ninhydrin Reagent and Compare with HPLC Method in Tablet - JALAL HOSSEINIMEHR*, SEYED; POURMORAD, FERESHTEH; MOSHTAGHI, EHSAN; AMINI†, MOHSEN (Asian Journal of Chemistry, 2024)
A simple and sensitive spectrophotometeric method has been developed for the determination of baclofen in tablet. Baclofen reacts with ninhydrin reagent in aqueous solution producing a coloured product. In this study, the different experimental parameters affecting the development and stability of the colour were carefully studied and optimized. The modified HPLC with ion pair method was used for quantification of baclofen in the same tablets that used with spectrophotometery. The absorbance-concentration plot is linear over the range 0.4-1.4 mg/mL with correlation coefficient of 0.995. The molar absorptive was 283.36 mol/L cm. The validity of the described procedures was assessed to show that this method had good validity at different times. Statistical analysis of the results has been carried out with F-test and T-test showed that it has high accuracy with HPLC method, but it has not good precision compared to HPLC method.